Ultrathin NiO confined within hollow carbon sphere for efficient electrochemical energy storage - Shi, Xiaoze; Zhang, Shuai; Chen, Xuecheng; Tang, Tao; Klingeler, Rüdiger; Mijowska, Ewa (Journal of alloys and compounds, 2019)
In this contribution, we present a facile encapsulating process for controlled synthesis of a hybrid structure of ultrathin NiO crystals confined growth on the interior shells of hollow carbon sphere (NiOHCS). In this method, a complete HCS with high porosity and good electrical conductivity can selectively confine the growth of NiO directly to its inner carbon shell. The as-prepared NiO@HCS offers advantages such as high surface area, great electrical conductivity and suitable pore size distribution. Besides, the small number of metal oxide nanocrystals inside HCS can provide more efficient electrochemical reaction within NiO compared with bulk NiO with large size. When used for a lithium-ion battery, NiO@HCS possesses the high capacity and superior rate capability as an anode material. Owing to the strong interaction of HCS and NiO crystals, NiO@HCS exhibits excellent cycle stability at a high current density. Furthermore, NiO@HCS also shows good capacitive performance in a symmetric supercapacitor device.